A Case Report: Physiotherapy Management for Patients with Plantar Fasciitis - Abyori Daru Murtama; Dwi Rosella Komala Sari; Warih Sri Widodo (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Plantar fasciitis is a common cause of heel pain that is often found in the population aged 40-60 years, especially women with prolonged standing activities and high body mass index. This case report discusses physiotherapy management in a 41-year-old female patient with plantar fasciitis dextra who underwent therapy at Panembahan Senopati Hospital. The physiotherapy interventions provided included ultrasound, gastrocnemius muscle massage, stretching (Towel Stretch), and exercises (Calf Raise and Towel Toe Curl) for three sessions in three weeks. Evaluation was performed using Wong Baker Scale, Manual Muscle Testing (MMT), Goniometer, and Foot and Ankle Disability Index (FADI). The results showed a decrease in tenderness and pain during movement, increased plantar fascia flexibility, and an increase in FADI score from 63.28% to 77.88%, indicating improved function. Physiotherapy interventions proved to be effective in managing plantar fasciitis symptoms conservatively and improving the patient's quality of life.